Bad-metal relaxation dynamics in a Fermi lattice gas - W. Xu (Nature Portfolio, 2019)
The origin of bad-metal resistivity is a long-standing problem for condensed matter physics. Here the authors show anomalous resistivity, transport lifetime, and relaxation dynamics consistent with bad-metal behavior over a wide range of temperature for fermionic potassium atoms in optical lattices.